Interes przedsiębiorcy wprowadzającego opakowania jednorazowego użytku z tworzyw sztucznych - Kułak-Krzysiak, Katarzyna (PRAWO i WIĘŹ, 2025)
Directive (EU) 2019/904 of the European Parliament and the Council on reducing the environmental impact of certain plastic products obliged EU member states to implement it into national law by 3 July 2021. The legal act intended to introduce the SUP Directive (Directive of the European Parliament and of the Council (EU) 2019/904, hereinafter Single-Use Plastics) into the Polish legal order is the Law on Amendments to the Law on Obligations of Entrepreneurs with respect to the Management of Certain Waste and the Product Fee and Certain Other Laws of 18 March 2021, marked in the Government Legislative Center with the signature: UC73. Poland had a time range to implement the recommended regulations. The SUP Directive applies to a wide range of businesses, including manufacturers, distributors, retailers and foodservice operators and end users. Anyone who markets single-use plastic products must comply with the new regulations. The year 2024 is a crucial one for both businesses and customers, as most of these regulations come into effect. One may ask what the new regulations mean for entrepreneurs who introduce single-use plastic products to the market? The directive on “plastics” is needed. Changes are needed to clarify the obligations of entrepreneurs in the field of single-use plastic packaging, and consumer education is needed in this area due to the deteriorating state of the natural environment. It should be stated that the introduction of regulatory solutions has become a significant step influencing the functioning of enterprises. This results from the scope of national and international regulations, which impose a number of restrictions on entrepreneurs related to the introduction of single-use plastic products to the market. It should be stated that the changes to date are beneficial because they affect the level of awareness of the harmfulness of single-use plastic products for the environment among both entrepreneurs and consumers, the need to recycle waste, or the use of alternative single-use or reusable products.